A perspective on multisensory integration and rapid perturbation responses. (May 2015) - Cluff, Tyler; Crevecoeur, Frédéric; Scott, Stephen H.
Highlights: Different brain areas and delays involved in visual and mechanical perturbations. Models of multisensory integration do not account for multiple feedback delays. Open questions and challenges identified for real-time multisensory integration. Abstract: In order to perform accurate movements, the nervous system must transform sensory feedback into motor commands that compensate for errors caused by motor variability and external disturbances. Recent studies focusing on the importance of sensory feedback in motor control have illustrated that the brain generates highly flexible responses to visual perturbations (hand-cursor or target jumps), or following mechanical loads applied to the limb. These parallel approaches have emphasized sophisticated, goal-directed feedback control, but also reveal that flexible perturbation responses are expressed at different latencies depending on what sensory system is engaged by the perturbation. Across studies, goal-directed visuomotor responses consistently emerge in muscle activity ∼100 ms after a perturbation, while mechanical perturbations evoke goal-directed muscle responses in as little as ∼60 ms (long-latency responses). We discuss the limitation of current models of multisensory integration in light of these asynchronous processing delays, and suggest that understanding how the brain performs real-time multisensory integration is an open question for future studies.